Medical claims-based case–control study of temporal relationship between clinical visits for hand syndromes and subsequent diabetes diagnosis: implications for identifying patients with undiagnosed type 2 diabetes mellitus. Issue 10 (20th October 2016) - Hou, Wen-Hsuan; Li, Chung-Yi; Chen, Lu-Hsuan; Wang, Liang-Yi; Kuo, Li-Chieh; Kuo, Ken N; Shen, Hsiu-Nien; Chiu, Chang-Ta
Abstract : Objectives: To investigate whether a temporal relationship is present between clinical visits for diabetes-related hand syndromes (DHSs) and subsequent type 2 diabetes mellitus (T2DM) diagnosis and, accordingly, whether DHSs can be used for identifying patients with undiagnosed T2DM. Design: This study had a case–control design nested within a cohort of 1 million people from the general population, which was followed from 2005 to 2010. The odds of prior clinical visits for DHSs, namely carpal tunnel syndrome (CTS), flexor tenosynovitis, limited joint mobility and Dupuytren's disease, were estimated for cases and controls. We used a conditional logistic regression model to estimate the OR and 95% CI of T2DM in association with a history of DHSs. The validity and predictive value of using the history of DHSs in predicting T2DM diagnosis were calculated. Setting: Taiwan National Health Insurance medical claims. Participants: We identified 33 571 patients receiving a new diagnosis of T2DM (cases) between 2005 and 2010. Each T2DM case was matched with 5 controls who had the same sex and birth year and were alive on the date of T2DM diagnosis. Primary and secondary outcome measures: The primary outcome measure was T2DM diagnosis. Results: The OR of T2DM in association with prior clinical visits was significantly increased for overall DHS and CTS, being 1.15 (95% CI 1.10 to 1.20) and 1.22 (95% CI 1.16 to 1.29), respectively. Moreover, 11% of patients with T2DM made clinical visits for CTS within 3 months prior to T2DM diagnosis. The history of DHSs had low sensitivity (<0.1% to 5.2%) and a positive predictive value (9.9% to 11.7%) in predicting T2DM. Conclusions: Despite the unsatisfactory validity and performance of DHSs as a clinical tool for detecting patients with undiagnosed T2DM, this study provided evidence that clinical visits for DHSs, particularly for CTS, can be a sign of undiagnosed T2DM.